Properties and Components of Recycled Engine Oil Bottom Rejuvenated Asphalt and Its Grey Relationship Analysis - Jin Li; Miaozhang Yu; Xinzhuang Cui; Wentong Wang (Advances in Materials Science and Engineering)
Numerous environmental pollution and resource waste problems are associated with recycled engine oil bottom (REOB), which cannot be effectively recycled. Based on the similarity compatibility theory and component adjustment theory, comparing the physical and rheological properties of laboratory-aged asphalt under three types of REOB (defined as REOB-1, REOB-2, and REOB-3) with different dosages, the optimum type and dosage of REOB as asphalt regenerant were explored. The rejuvenation mechanism of REOB on aged asphalt was revealed by combined performance, four-component, and infrared spectroscopy analyses. The relationship between the four components and physical rheological indexes in the process of asphalt rejuvenated by REOB was quantitatively obtained by the grey relationship analysis. The results show that only REOB-3 with a dosage of 7% on the aged asphalt has the best comprehensive rejuvenation effect. Also, the high-temperature rutting resistance of rejuvenated asphalt with 7% REOB-3 is better than that of the original asphalt, but the low-temperature flexibility and the crack resistance performance have yet to be improved. The mechanism through which REOB rejuvenates aged asphalt is an incomplete component adjustment; some of the components undergo physical or chemical reactions and transformations. Accordingly, the asphaltene content and the intensity of sulfoxide functional groups in aged asphalt decrease, thereby achieving rejuvenation gradually with the addition of REOB. A grey relationship analysis demonstrates that asphaltenes have the greatest influence on high-temperature performance and that low-temperature performance requires a reasonable combination of four components. Moreover, a comprehensive advantage analysis reveals that REOB is the most sensitive to the softening point and that the asphaltene content has the greatest influence on the physical and rheological properties of REOB-rejuvenated asphalt. Therefore, the asphaltene content should be strictly controlled during the addition of REOB to rejuvenate aged asphalt.